2017
DOI: 10.1177/1074248417725058
|View full text |Cite
|
Sign up to set email alerts
|

Carvedilol Inhibits Matrix Metalloproteinase-2 Activation in Experimental Autoimmune Myocarditis: Possibilities of Cardioprotective Application

Abstract: The protective effects of carvedilol on heart function observed in the acute phase of experimental autoimmune myocarditis seem to be associated with its ability to decrease MMP-2 activity and subsequently prevent degradation of myofilaments and release of troponin I while not related to suppression of inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
3
11
0
Order By: Relevance
“…Guttierez et al showed increased enzymatic activity for MMP-2 and MMP-9 in heart tissue during the acute phase of experimental Trypanosoma cruzi infection and significant decrease of heart inflammation, delayed peak in parasitemia, and improved survival rates as a result of inhibition of MMPs activity (19). In our previous study, we also showed that experimental autoimmune myocarditis in rats proceeded with an enhanced activation of MMPs in heart tissue and that inhibition of MMP-2 activity by carvedilol resulted in the reduction of troponin and myofilaments degradation and subsequent prevention of dysfunction of the mechanical function of the heart [16].…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Guttierez et al showed increased enzymatic activity for MMP-2 and MMP-9 in heart tissue during the acute phase of experimental Trypanosoma cruzi infection and significant decrease of heart inflammation, delayed peak in parasitemia, and improved survival rates as a result of inhibition of MMPs activity (19). In our previous study, we also showed that experimental autoimmune myocarditis in rats proceeded with an enhanced activation of MMPs in heart tissue and that inhibition of MMP-2 activity by carvedilol resulted in the reduction of troponin and myofilaments degradation and subsequent prevention of dysfunction of the mechanical function of the heart [16].…”
Section: Discussionmentioning
confidence: 85%
“…Other interesting and promising treatment options may be strategies of preventing oxidative stress-related destruction of contractile proteins [16,18]. Oxidative stress related to acute ischemia-reperfusion injury of the heart muscle leads to intracellular activation of MMPs and subsequent degradation of troponin I, myosin light chain-1, α-actinin, and titin [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At this moment, there is no effective standardized therapy for acute myocarditis, besides the optimal care of heart failure and arrhythmias in accordance with evidence-based guidelines and specific etiology-driven therapy [7,8].…”
Section: Discussionmentioning
confidence: 99%